2021
DOI: 10.1021/acsami.1c07610
|View full text |Cite
|
Sign up to set email alerts
|

Strong Electron Acceptor of a Fluorine-Containing Group Leads to High Performance of Perovskite Solar Cells

Abstract: Organic−inorganic hybrid perovskites have become one of the most promising thin-film solar cell materials owing to their remarkable photovoltaic properties. However, nonradiative recombination of carriers usually leads to inferior performance of perovskite (PVK) devices. Interface modification is one of the effective ways to improve separation of charges for perovskite solar cells (PSCs). Here, a small organic molecule of tetrafluorophthalonitrile (TFPN) is used to enhance the extraction and transportation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 57 publications
3
20
0
Order By: Relevance
“…The much weaker Si-O peak of the modified perovskite film compared to VTMES manifest that VTMES connected with perovskite by forming PbO bonding due to oxydic properties of ionic oxygen atoms. [28,36] In addition, Figure S2 (Supporting Information) shows X-ray photoelectron spectroscopy (XPS) of control and modified perovskite films. Pb 4f peaks shift from 138.20 and 143.10 eV to 138.41 and 143.25 eV (Figure S2b, Supporting Information), and O 1s peak shift from 532.34 to 532.56 eV (Figure S2c, Supporting Information) for control and VTMES-modified films, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The much weaker Si-O peak of the modified perovskite film compared to VTMES manifest that VTMES connected with perovskite by forming PbO bonding due to oxydic properties of ionic oxygen atoms. [28,36] In addition, Figure S2 (Supporting Information) shows X-ray photoelectron spectroscopy (XPS) of control and modified perovskite films. Pb 4f peaks shift from 138.20 and 143.10 eV to 138.41 and 143.25 eV (Figure S2b, Supporting Information), and O 1s peak shift from 532.34 to 532.56 eV (Figure S2c, Supporting Information) for control and VTMES-modified films, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, with 3 mg mL −1 VTMES modification, the intensity of perovskite (110) and (220) plane is enhanced, and the corresponding PbI 2 peak is obviously restrained, demonstrating that VTMES is of great importance to promote the crystallization of perovskite crystal during the post-treatment process to contribute the conversion from PbI 2 to perovskite phase. [27,28] A small amount of excessive PbI 2 can passivate defects, which is conducive to improving the quality of perovskite films. [24] However, too much quantity of PbI 2 would restrain grain growth of perovskite, thus leading to grain boundary defects and inferior stability.…”
Section: Resultsmentioning
confidence: 99%
“…Meanwhile, the Pb 4 f peak between PbI 2 and MSTC‐PbI 2 is shifted from 138.19 and 143.09 eV to 138.51 and 143.43 eV (Figure 2e), and the O 1 s (532.27–532.52 eV) and the N 1 s (400.18–400.43 eV) (Figure 2f) peak shift between FAI and MSTC‐FAI, further indicating that MSTC could produce chemical connections with PbI 2 and FAI precursor. The shift of Pb 4 f , O 1 s , and N 1 s XPS spectra (Figure S8, Supporting Information) between control, MSTC‐PbI 2 , and MSTC‐FAI perovskite films, respectively, suggests that Pb 2+ could coordinate with O and N atoms in MSTC because the lone pair electrons of O and N would fill the empty orbital of unsaturated Pb 2+ ; [ 17 ] thus, PbI 2 defects have been greatly restrained after the addition of MSTC, in consistent with the XRD results. The coordination bonding of chemical connection between perovskite and MSTC is depicted in Figure 2g.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, it is found that when the concentration increases to 60 ppm, there is a decrease of perovskite surface morphology and absorption. The reason for this might be that an excess amount of d -tryptophan remains on the surface of perovskite, which decreases the crystallinity of the perovskite film as shown in Figure f …”
Section: Resultsmentioning
confidence: 99%